High Prevalence of Anal and Oral High-Risk Human Papillomavirus in Human Immunodeficiency Virus–Uninfected French Men Who Have Sex With Men and Use Preexposure Prophylaxis. (19th June 2019) - Mboumba Bouassa, Ralph-Sydney; Bélec, Laurent; Gubavu, Camelia; Péré, Hélène; Matta, Mathieu; Maka, Artur; Puech, Julien; Tonen Wolyec, Serge; Veyer, David; Gravier, Anne; Hocqueloux, Laurent; Prazuck, Thierry
Abstract: Background: We assessed the prevalence and risk factors of anal and oral high-risk (HR) human papillomavirus (HPV) infection in human immunodeficiency virus–uninfected men who have sex with men (MSM) and take preexposure prophylaxis (PrEP) in France. Methods: Anal and oral samples were screened by multiplex real-time polymerase chain reaction (Anyplex II HPV 28; Seegene) for HPV DNA. Results: A total of 61 unvaccinated MSM (mean age, 36.1 years) were enrolled. Anal HPV and HR-HPV prevalences were 93.4% and 81.9%, respectively, and oral HPV and HR-HPV prevalences, 33.9% and 19.6%, respectively. HR-HPV type 33 was the most detected genotype, in both anal and oral samples. Among MSM, 68.8% carried ≥1 anal HPV type targeted by the 9-valent Gardasil-9 vaccine; all oral HPV-positive samples carried ≥1 strain included in the vaccine. Condomless receptive anal intercourse and history of anal gonorrhea were the main factors associated with increased risk for anal HPV infection (adjusted odds ratio, 10.4) and anal infection with multiple HR-HPV genotypes (5.77), respectively. Conversely, having had <10 partners in the last 12 months was associated with decreased risk for anal carriage of both multiple HPV (adjusted odds ratio, 0.19) and HR-HPV (0.17) types. Conclusion: French MSM using PrEP are at high risk for both anal and oral carriage of HR-HPV that could lead to HPV-related cancers. Abstract : French MSM using PrEP are at high risk for both anal and oral carriage of HR-HPV. Although PrEP alone constitutes a promising tool for reducing and preventing HIV in MSM, it remains necessary to associate PrEP with sexual health interventions.